Embedded inscriptions in Herodotus and Thucydides - Allgaier, Benjamin (Harrassowitz Verlag, 2022)
The two founding works of the Western historiographical tradition, Herodotus’ Histories and Thucydides’ History, feature, among many other things, mentions and quotations of inscriptions (that is, texts written on durable materials such as stone). This book explores the epigraphic dimension of Herodotus’ Histories and Thucydides’ History (including potential allusions to inscriptions in general, possible instances of a tacit use of epigraphically recorded information, and explicit references to specific inscriptions) and offers a number of case studies aimed at elucidating the subtle uses to which specific embedded inscriptions are put in the works of Herodotus and Thucydides. Special attention is paid to the ways in which these inscriptions contribute to the characterisation of historical actors and to the self-fashioning of the Herodotean and Thucydidean narrator. The book may appeal to literary classicists, ancient historians, epigraphists, and other readers with an interest in ancient historiography and/or epigraphic culture.
Keywords: Herodotus -- Criticism, Textual; Thucydides -- Criticism, Textual; Hochschulschrift; Inschrift; Thucydides / Historiae; Herodotus / Historiae